Alpha EEG Spectral Characteristics in the Parieto-Occipital lobe of Elderly Patients with Chronic Insomnia and Mild Cognitive Impairment - GUO Zhenxing; BAI Linxin; ZHANG Lin; GAO Jiahui; RAO Ting; LIU Zhizhen (康复学报)
ObjectiveAnalysis of Alpha Spectral Characteristics in the Parieto-Occipital lobe of Elderly Individuals with Chronic Insomnia and Mild Cognitive Impairment （MCI）.MethodsEighty elderly individuals with chronic insomnia and mild cognitive impairment （MCI） were selected from the community in Fuzhou, Fujian Province, from June 2019 to December 2020. This included a healthy control group （HC） of30 individuals, a chronic insomnia group （CI） of 20 individuals, and a chronic insomnia with MCI group （CI-MCI） of 30 individuals. The Pittsburgh Sleep Quality Index （PSQI） was used to assess sleep quality, while the Fuzhou version of the Montreal Cognitive Assessment （MoCA） was employed to evaluate cognitive functions, including visuospatial execution, naming, attention, verbal fluency, abstraction, delayed recall, and orientation. Daytime resting-state electroencephalography （EEG） was collected using the Neuroscan synchronous EEG recording system, comparing the power values and trends of alpha waves （8–13 Hz） across channels in the occipital lobe. Additionally, we analyzed the changes in alpha spectral power in relation to cognitive functions.Results（1）PSQI scores：Compared to the HC group, the daytime functional impairment scores in the CI-MCI group were significantly higher, with a statistically significant difference （P <0. 05）. The total PSQI scores, sleep quality, sleep onset latency, total sleep time, sleep efficiency, and sleep disturbance scores were significantly higher in the CI group and the CI-MCI group, while the use of hypnotics score was significantly reduced, with statistically significant differences （P <0. 05）. （2）MoCA scores：Compared to the HC and CI groups, the CI-MCI group exhibited significantly lower total MoCA scores, as well as reductions in visuospatial execution, naming, attention, verbal fluency, delayed recall, and orientation, with statistically significant differences （P <0. 05）. （3）EEG spectral characteristics：Compared to the HC group, the CI-MCI group showed significantly increased alpha spectral power at sites P1, P6, POZ, PO4, and PO6 in the Parieto-Occipital lobe, with statistically significant differences （P <0. 05）. Additionally, the topographical maps of the alpha spectral power in the parietal and occipital lobes were notably stronger in the CI-MCI group compared to the HC group. （4）Correlation between changes in occipital alpha spectral power and cognitive function：The alpha spectral power at site P6 in the right parietal lobe （r =0. 444, P =0. 023）, at site POZ in the occipital lobe （r =0. 444, P =0. 023）, and at site PO4 in the right parietal lobe （r =0. 478, P =0. 014） all showed a positive correlation with visuospatial executive function.ConclusionThe changes in Parieto-Occipital lobe alpha spectral power are indicative of cognitive impairment in elderly individuals with chronic insomnia and mild cognitive impairment （MCI）. Moreover, Parieto-Occipital lobe alpha spectral power can modulate cognitive function in this population.